Neuroprotective actions of vitamin C in rat striatum after pilocarpine-induced seizures (Archives of Clinical Psychiatry, 2010)
BACKGROUND: Seizures may produce neuronal damage in several areas and especially in limbic structures. OBJECTIVES: This study aimed to evaluate the neuroprotective effects of vitamin C in the histopathological changes observed in rat striatum after seizures. MATERIAL AND METHODS: Healthy Wistar rats were divided into four groups. The first group was treated with 0.9% saline (control group) and the second one with pilocarpine (400 mg/kg, P400 group). Third and fourth groups were treated with vitamin C (250 mg/kg), 30 minutes before receiving P400 (P400 + VIT C group) or 0.9% saline (VIT C group), respectively. After the treatments, all groups were observed for 24 hours, sacrificed and dissected out to remove their brains for histopathological analysis. RESULTS: The group P400 presented seizures that progressed to status epilepticus in 75% of the animals. Pretreatment with vitamin C produced a 35% reduction in this index. P400 and P400 + VIT C groups revealed 80% and 20% of animals with brain injury, respectively. In P400 group, lesion severity of the striatum was 50%. In turn, in striatal region of animals treated with P400 + VIT C group, we detected a reduction of 40% in the severity degree. DISCUSSION: Pilocarpine-induced seizures are installed by the cholinergic system and propagated by free radicals and by glutamatergic system, leading to brain damage. The antioxidant drugs may have therapeutic potential for epileptic patients to protect against brain injure through removing free radicals produced, suggesting that vitamin C may influence epileptogenesis and promote neuroprotective actions during seizures.